Modeling optical constants from the absorption of organic thin films using a modified Lorentz oscillator model - Dutta, Arpan; Tiainen, Ville; Qureshi, Hassan Ali; Duarte, Luís; Toppari, J. Jussi (Optical materials express, 2022)
Optical constants of organic thin films can be evaluated using the Lorentz oscillator model (LOM) which fails to fit inhomogeneously broadened absorption of highly concentrated molecular films. In modified LOM (MLOM), the inhomogeneous broadening is implemented through a frequency-dependent adjustable broadening function. In this work, we evaluate the optical constants of rhodamine 6G doped poly-vinyl alcohol thin films with varying doping concentration (including also extensively high concentrations) using MLOM, which outperforms LOM by showing a better agreement with the experimental results. Our proposed method provides a way to accurately determine optical constants of isotropic organic thin films only from their absorption spectra without spectroscopic ellipsometry.